Structural color film and preparation method thereof

By filling the high-strength flame retardant polymer into the gap of the modified hollow SiO2 photonic crystal template, a structural color film with excellent flame retardant and mechanical strength was prepared, which solved the problems of poor mechanical stability and high flammability of existing structural color materials in harsh environments, and achieved effective application in high-temperature flammable places.

CN119684789AActive Publication Date: 2025-03-25GAOYOU YUNTIAN OPTICAL DOMAIN TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411567246.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-25
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing structural colored materials have poor mechanical stability and high flammability in harsh environments, which limits their application in high-temperature flammable places.

Method used

A hollow SiO2 photonic crystal template was combined with a high-strength flame retardant polymer, and the template was modified by a silane coupling agent and then filled with the polymer, to prepare a structural color film with excellent flame retardant, high mechanical strength and high temperature resistance.

Benefits of technology

It has achieved excellent flame retardancy, structural stability, and strong acid and alkali resistance in harsh environments. The film remains bright in tensile stress and friction tests, with an ultimate oxygen index of more than 33%, and a flame retardant grade of V-0.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684789A_ABST
    Figure CN119684789A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of structural color materials, and particularly relates to a structural color film and a preparation method thereof.The structural color film comprises a hollow SiO2 photonic crystal template and a high-strength flame-retardant polymer filled in gaps of the hollow SiO2 photonic crystal template; wherein the hollow SiO2 photonic crystal template is modified by a silane coupling agent and then is filled with a high-strength flame-retardant polymer. According to the structural color film disclosed by the invention, a polymer with flame retardance and high mechanical strength is taken as a target filling material, a modified hollow SiO2 photonic crystal template is taken as a template, and gaps of the template are filled with the polymer, so that the structural color film with severe environment resistance is obtained. The structural color film shows excellent flame retardance, structural stability, strong acid resistance and strong alkali resistance in a severe environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of structural color materials, and in particular relates to a structural color film and a preparation method thereof. Background Art

[0002] Structural color materials have the advantages of high saturation, high brightness, and no fading, and have important application value in the field of color display. The common photonic crystal structural color materials formed by point contact between microspheres have poor mechanical stability, which seriously limits their application. In addition, the current application scope of structural color materials is difficult to expand to harsh environments, such as high temperature, strong acid and alkaline environments. Combining special polymers with photonic crystal structural color materials can give structural color materials high mechanical strength and functionality, which provides an effective way to expand the application scope of structural color materials. However, commonly used polymers are flammable, which limits the application of polymer-based structural color materials in high temperature and flammable places.

[0003] Therefore, there is an urgent need in this field to develop structural color materials with excellent flame retardancy, high strength, high temperature resistance and corrosion resistance. Summary of the invention

[0004] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to at least solve one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a structural color film and a preparation method thereof that meet one or more of the above-mentioned needs.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] A structural color film comprises a hollow SiO2 photonic crystal template and a high-strength flame-retardant polymer filled in the gap of the hollow SiO2 photonic crystal template; wherein the hollow SiO2 photonic crystal template is modified by a silane coupling agent and then filled with the high-strength flame-retardant polymer.

[0007] As a preferred solution, the high-strength flame-retardant polymer is one or a combination of poly(m-phenylene isophthalamide) PMIA, poly(p-phenylene terephthalamide) PPTA, and poly(benzimidazole) PBI.

[0008] As a preferred embodiment, the silane coupling agent is one or a combination of aminopropyltriethoxysilane APTES, methacryloxypropyltrimethoxysilane MPS, and methyltrimethoxysilane MTMS.

[0009] The present invention also provides a method for preparing the structural color film as described in any of the above schemes, comprising the following steps:

[0010] (1) Preparation of hollow SiO2 photonic crystal template;

[0011] (2) Modifying the hollow SiO2 photonic crystal template using a silane coupling agent;

[0012] (3) Filling the gaps of the modified hollow SiO2 photonic crystal template with a high-strength flame-retardant polymer and vacuum drying the template to obtain a structural color film.

[0013] The invention uses an emulsion polymerization method to prepare monodisperse polymer nano-microspheres with uniform particle size, hydrolyzes tetraethyl silicate TEOS to coat a layer of SiO2 on the surface of the polymer nano-microspheres to prepare core-shell microspheres, disperses the core-shell microspheres to obtain a core-shell microsphere assembly liquid, utilizes the core-shell microspheres to self-assemble to form a photonic crystal template, and calcines to form a hollow SiO2 photonic crystal template, referred to as an H-SiO2 PCs template; the H-SiO2 PCs template is placed in a mixed solution prepared by a silane coupling agent, ethanol and water in a certain volume ratio, and is heated at a certain temperature for a period of time to obtain a modified H-SiO2 PCs template; an organic solvent and a co-solvent are added to a polymer with flame retardancy and high mechanical strength, heated and stirred until the polymer is completely dissolved to obtain a transparent polymer solution, which is dripped onto the modified H-SiO2 PCs template, and the solvent is completely volatilized by high-temperature vacuum drying to obtain a structural color film for harsh environments.

[0014] As a preferred solution, the step (2) specifically comprises:

[0015] The hollow SiO2 photonic crystal template is placed in a mixed solution of a silane coupling agent, ethanol and water for hydrothermal reaction to obtain a modified hollow SiO2 photonic crystal template.

[0016] As a preferred embodiment, the volume ratio of the silane coupling agent, ethanol and water in the mixed solution is (0.05-0.2):20:(0.5-1.5).

[0017] As a preferred embodiment, the temperature of the hydrothermal reaction is 75-85° C. and the duration is 1-3 hours.

[0018] As a preferred solution, the step (3) specifically comprises:

[0019] Adding a high-strength flame-retardant polymer to an organic solvent and a co-solvent, stirring at 70 to 100° C. for 10 to 20 hours to completely dissolve the polymer, and obtaining a transparent polymer solution with a mass fraction of 8 to 10%, and then filling the gaps of the modified hollow SiO2 photonic crystal template;

[0020] The organic solvent is one or a combination of N,N-dimethylacetamide DMAc, dimethyl sulfoxide DMSO, N-methylpyrrolidone NMP, N,N-dimethylformamide DMF, and hexamethylphosphoramide HMPA; and the co-solvent is one or a combination of lithium chloride, calcium chloride, sodium hydroxide, and potassium hydroxide.

[0021] As a preferred embodiment, the mass ratio of the organic solvent to the co-solvent is (20-30):1.

[0022] As a preferred embodiment, the amount of the transparent polymer solution is determined according to the surface area of ​​the hollow SiO2 photonic crystal template and is 0.1 to 0.3 mL / cm 2 .

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The structural color film of the present invention uses a polymer with flame retardancy and high mechanical strength as the target filling material, and uses the modified H-SiO2 PCs as a template to fill the polymer into the gap of the template to obtain a structural color film that is resistant to harsh environments. The structural color film exhibits excellent flame retardancy, structural stability, and resistance to strong acids and alkalis in harsh environments. Before and after tests such as large tensile stress and friction, the structural color of the film remains bright; at the same time, the limiting oxygen index of the film reaches more than 33%, and the flame retardant grade reaches V-0, showing excellent flame retardancy. Based on the above-mentioned excellent performance exhibited in harsh environments, the structural color film of the present invention has broad application prospects in color display in the fields of high temperature resistance, flame retardant protection, and fire passage markings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 In the figure, a is the preparation flow chart of PMIA / H-SiO2 PCs structural color film; b is the optical photograph of PS@SiO2PCs template, modified H-SiO2 PCs template and PMIA / H-SiO2 PCs structural color film; c is the reflectance spectrum of PS@SiO2 PCs template, modified H-SiO2 PCs template and PMIA / H-SiO2PCs structural color film; d is the CIE chromaticity diagram of PS@SiO2 PCs template, modified H-SiO2 PCs template and PMIA / H-SiO2 PCs structural color film;

[0026] Figure 2 The contact angle images of the polymer solution of Example 1 of the present invention before and after modification of the H-SiO2 PCs template are shown;

[0027] Figure 3In the figure, a, b, and c are optical photographs of three PMIA / H-SiO2 PCs structural color films with a shell thickness of 32 nm, which are prepared using PS microspheres with particle sizes of 206 nm, 242 nm, and 266 nm, respectively; d is the reflection spectra of the three PMIA / H-SiO2 PCs structural color films; e is the CIE chromaticity diagram of the three PMIA / H-SiO2 PCs structural color films; f is the photograph and reflection spectrum of the PMIA / H-SiO2 PCs structural color film with a shell thickness of 32 nm, which is prepared using PS microspheres with a particle size of 266 nm, at different incident angles;

[0028] Figure 4 In the figure, a is a schematic diagram of the tensile test of PMIA / H-SiO2 PCs structural color film; b is a stress-strain curve of PMIA / H-SiO2 PCs structural color film and pure PMIA film; c is a photo of PMIA / H-SiO2 PCs structural color film under loads of 0.5kg and 1kg respectively; d and e are the reflection spectra of PMIA / H-SiO2 PCs structural color film under different tensile stresses and the comparison of the position of the reflection spectrum peak and the reflectivity respectively;

[0029] Figure 5 In the figure, a and b are optical photos of PMIA / H-SiO2 PCs structural color film during strong acid and strong alkali resistance tests, respectively, and c and d are reflectance spectra of PMIA / H-SiO2 PCs structural color film after strong acid and strong alkali resistance tests, respectively;

[0030] Figure 6 In the figure, a is a liquid nitrogen resistance test photo of PMIA / H-SiO2 PCs structural color film; b is a liquid nitrogen brittle fracture resistance test photo of PMIA / H-SiO2 PCs structural color film; c and d are the reflectance spectra of PMIA / H-SiO2 PCs structural color film in liquid nitrogen resistance test and liquid nitrogen brittle fracture resistance test respectively;

[0031] Figure 7 In the figure, a is a schematic diagram of the vertical combustion test of PMIA / H-SiO2 PCs structural color film; b is a comparison chart of the limiting oxygen index of PMIA / H-SiO2 PCs structural color films with different structural colors and pure PMIA film; c is a photo of the vertical combustion test of PMIA / H-SiO2 PCs structural color film. DETAILED DESCRIPTION

[0032] In order to more clearly illustrate the embodiments of the present invention, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings and other implementation methods can be obtained based on these accompanying drawings without creative work.

[0033] Embodiment 1:

[0034] In this embodiment, PS monodisperse nanospheres with uniform particle size are prepared by emulsion polymerization. The PS microspheres are uniformly dispersed in a mixed solution of anhydrous ethanol, deionized water and ammonia water. Under magnetic stirring, tetraethyl silicate TEOS is quickly added to the above solution, and stirring is continued for a period of time at room temperature to obtain PS@SiO2 core-shell microspheres. The concentration of the PS@SiO2 dispersion is adjusted to 2.4%. Under constant temperature conditions, the PS@SiO2 core-shell microspheres are self-assembled for 8 hours to form a PS@SiO2 PCs template on the hydrophilized base surface. The PS@SiO2 PCs template is placed in a muffle furnace and heated to 500°C. After cooling to room temperature, an H-SiO2 PCs template is obtained. The specific preparation process of the H-SiO2 PCs template belongs to the prior art and will not be repeated here.

[0035] The H-SiO2 PCs template was placed in a hydrothermal autoclave containing a mixed solution of methacryloxypropyltrimethoxysilane MPS, ethanol and water in a volume ratio of 0.1:20:1, and heated at 80°C for 2h to obtain a modified H-SiO2PCs template.

[0036] Add poly(m-phenylene isophthalamide) PMIA to N,N-dimethylacetamide DMAc and LiCl, stir at 90°C for 10 hours to completely dissolve it, and obtain a transparent polymer solution with a mass fraction of 10%; wherein the mass ratio of N,N-dimethylacetamide DMAc to LiCl is 30:1;

[0037] The polymer solution was added dropwise onto the surface of the modified H-SiO2 PCs template. After the polymer solution was evenly leveled, it was quickly moved into a vacuum drying oven, evacuated to 0.003 MPa, slowly heated to 100°C and continued to heat for 2 h to completely evaporate the solvent to obtain a PMIA / H-SiO2 PCs structural color film.

[0038] The amount of polymer solution used is determined according to the surface area of ​​the hollow SiO2 photonic crystal template and is 0.2 mL / cm 2 .

[0039] In this example, PS microspheres with a particle size of 266 nm were used as the core material, and PS@SiO2 core-shell microspheres with a shell thickness of 32 nm were used as the constituent units of the PS@SiO2 PCs template. PMIA was infiltrated into the gaps of the modified H-SiO2 PCs template to prepare a PMIA / H-SiO2 PCs high-strength flame-retardant structural color film. Figure 1 a is the preparation process of PMIA / H-SiO2 PCs high-strength flame-retardant structural color film. PS@SiO2 core-shell microspheres are self-assembled to form PS@SiO2 PCs templates, which are then calcined and modified to form H-SiO2 PCs templates. PMIA polymer is filled into the gaps of the modified template to obtain PMIA / H-SiO2 PCs high-strength flame-retardant structural color film. Figure 1 b is the optical photograph of the PS@SiO2 PCs template, the modified H-SiO2 PCs template and the PMIA / H-SiO2 PCs high-strength flame-retardant film, whose colors are green, blue and cyan respectively. Figure 1 c is Figure 1 b Reflection spectra of the corresponding samples. After calcination, the PS core of the core-shell microspheres was removed from the PS@SiO2 PCs template, and the average refractive index of the template decreased, causing the position of the reflection peak to blue-shift from 513nm (green) of the PS@SiO2 PCs template to 390nm (blue) of the H-SiO2 PCs template. When PMIA was filled into the gap of the H-SiO2 PCs template to form a PMIA / H-SiO2 PCs film, the average refractive index increased significantly, and the position of the reflection peak red-shifted to 488nm (cyan). Figure 1 d is the CIE chromaticity diagram of the three samples, and the color and Figure 1 The colors of the optical photograph of b are basically the same.

[0040] Figure 2 The PMIA solution was dropped onto the H-SiO2 PCs template before and after modification, respectively. The contact angle image after 10 minutes showed that the PMIA solution had a smaller contact angle on the modified template, which indicated that its wettability on the template was better, which was conducive to the smoother penetration of the PMIA solution into the template gap.

[0041] Figure 3 a. Figure 3 b and Figure 3 c are optical photographs of three PMIA / H-SiO2 PCs high-strength flame-retardant films with a shell thickness of 32 nm, which were prepared in Example 1 using PS microspheres with particle sizes of 206 nm, 242 nm, and 266 nm, respectively. Figure 3d is the reflection spectrum of the three films, and their reflection peak positions are 514nm, 617nm and 660nm respectively. The larger the particle size of H-SiO2 in the film, the larger the inter-crystalline spacing. According to Bragg's law, the wavelength position of the film reflection peak will also increase accordingly. Figure 3 e is the CIE chromaticity diagram of the three films, and the chromaticity points corresponding to the films are basically consistent with their optical photographs. Figure 3 f is Figure 3 c's photos and reflection spectra at different incident angles. According to Bragg's law, as the incident angle of light increases, the position of the film's reflection peak will gradually shift to the blue. The film's structural color will also gradually change from red to smaller wavelengths.

[0042] Figure 4 a is a schematic diagram of the tensile test of the PMIA / H-SiO2 PCs high-strength flame-retardant structural color film of this embodiment, Figure 4 b is the stress-strain curve of PMIA / H-SiO2 PCs film and pure PMIA film. The fracture strength and fracture strain of PMIA / H-SiO2 PCs film are 66MPa and 12%, respectively, which are higher than 57MPa and 6% of pure PMIA film, indicating that PMIA / H-SiO2 PCs film has excellent mechanical properties. Figure 4 c is the photo of PMIA / H-SiO2 PCs film under loads of 0.5kg and 1kg respectively. It can be seen from the photo that its structural color does not change significantly. Figure 4 d and Figure 4 e are the reflection spectra of PMIA / H-SiO2 PCs films under different tensile stresses, as well as the positions of the reflection spectrum peaks and the reflectivity. The above optical properties of the film did not change significantly under different tensile stresses, indicating that the structural color of the film has excellent stability under tensile stress.

[0043] Figure 5 a and Figure 5 b is an optical photograph of the PMIA / H-SiO2 PCs high-strength flame-retardant structural color film of this embodiment in the strong acid and strong alkali resistance test. The film was subjected to acid and alkali resistance tests. The film was immersed in a sulfuric acid solution with a pH of 1 for 7 days and in a sodium hydroxide solution with a pH of 14 for 7 days. The film remained intact and the structural color was basically unchanged. Figure 5 c and 5d are the reflection spectra of the film after strong acid and strong alkali resistance tests, respectively. After a long period of acid and alkali resistance test, the structural color and reflection spectrum of the film did not change significantly, verifying the excellent acid and alkali resistance of the film.

[0044] The film was tested for low temperature brittle fracture resistance in liquid nitrogen. Figure 6a is a liquid nitrogen resistance test photo of the PMIA / H-SiO2PCs high-strength flame-retardant structural color film of this embodiment, Figure 6 b is the photo of the film's resistance to liquid nitrogen brittle fracture test. Figure 6 c and Figure 6 d are the reflection spectra of the film in the liquid nitrogen resistance test and the liquid nitrogen brittle fracture resistance test. These photos and spectral test results show that the structural color and reflection spectrum of the film have not changed significantly, verifying that its structural color has excellent stability at low temperatures. Figure 6 e is the stress-strain curve of the film before and after the low-temperature resistance test. After the film was immersed in liquid nitrogen for 6 hours, the mechanical properties only decreased to a small extent.

[0045] The film was subjected to limiting oxygen index test and vertical burning test. Figure 7 a is a schematic diagram of a vertical combustion test of the PMIA / H-SiO2PCs high-strength flame-retardant structural color film of this embodiment, Figure 7 b is the limiting oxygen index of PMIA / H-SiO2 PCs films with different structural colors and pure PMIA films. The limiting oxygen index of PMIA / H-SiO2 PCs films with different structural colors is higher than 33% (flame-retardant material level) and higher than pure PMIA (29.1%). This shows that adding H-SiO2 PCs template to the composition is conducive to achieving higher flame retardant properties. Figure 7 As shown in c, the photo shows that the film that was ignited multiple times extinguished itself quickly without producing any molten droplets, and the flame retardant grade reached the highest V-0 grade, indicating that the film has excellent flame retardant properties.

[0046] Embodiment 2:

[0047] In this embodiment, PS monodisperse nanospheres with uniform particle size are prepared by emulsion polymerization. PS microspheres are uniformly dispersed in a mixed solution of anhydrous ethanol, deionized water and ammonia water. TEOS is quickly added to the above solution under magnetic stirring, and stirring is continued for a period of time at room temperature to obtain PS@SiO2 core-shell microspheres. The concentration of the PS@SiO2 dispersion is configured to be 2.4%. Under constant temperature conditions, the PS@SiO2 core-shell microspheres are self-assembled for 8 hours to form a PS@SiO2PCs template on the hydrophilized base surface. The PS@SiO2 PCs template is placed in a muffle furnace and heated to 500°C. After cooling to room temperature, the H-SiO2 PCs template can be obtained. It is placed in a hydrothermal kettle containing a mixed solution of MPS, ethanol and water in a volume ratio of 0.05:20:1.5. After heating at 75°C for 3 hours, the modified H-SiO2PCs template is obtained.

[0048] Add poly(p-phenylene terephthalamide) (PPTA) to dimethyl sulfoxide (DMSO) and NaOH, stir at 100°C for 15 hours to completely dissolve the poly(p-phenylene terephthalamide) (PPTA) to obtain a transparent polymer solution with a mass fraction of 8%; wherein the mass ratio of dimethyl sulfoxide (DMSO) to NaOH is 25:1;

[0049] The polymer solution was added dropwise onto the surface of the modified template. After the polymer solution was evenly leveled, it was quickly moved into a vacuum drying oven, evacuated to 0.003 MPa, slowly heated to 100°C and continued to heat for 2 hours to completely evaporate the solvent, thereby obtaining a PPTA / H-SiO2 PCs structural film.

[0050] The amount of polymer solution used is determined according to the surface area of ​​the hollow SiO2 photonic crystal template and is 0.3 mL / cm 2 .

[0051] Embodiment 3:

[0052] PS monodisperse nanospheres with uniform particle size were prepared by emulsion polymerization. PS microspheres were uniformly dispersed in a mixed solution of anhydrous ethanol, deionized water and ammonia water. TEOS was quickly added to the above solution under magnetic stirring and stirred for a period of time at room temperature to obtain PS@SiO2 core-shell microspheres. Under constant temperature conditions, PS@SiO2 core-shell microspheres were self-assembled for 8 hours to form PS@SiO2 PCs templates on the hydrophilized substrate. The PS@SiO2 PCs template was placed in a muffle furnace and heated to 500℃. After cooling to room temperature, the H-SiO2 PCs template was obtained. It was placed in a hydrothermal autoclave containing a mixed solution of MPS, ethanol and water in a volume ratio of 0.2:20:0.5. After heating at 85℃ for 1 hour, the modified H-SiO2 PCs template was obtained.

[0053] Add polybenzimidazole PBI to N-methylpyrrolidone NMP and CaCl2, stir at 70°C for 20 hours to completely dissolve it, and obtain a transparent polymer solution with a mass fraction of 9%; wherein the mass ratio of N-methylpyrrolidone NMP to CaCl2 is 20:1;

[0054] The polymer solution was added dropwise onto the surface of the modified template. After the polymer solution was evenly leveled, it was quickly moved into a vacuum drying oven, evacuated to 0.003 MPa, slowly heated to 100°C and continued to heat for 2 h to completely evaporate the solvent to obtain a PBI / H-SiO2 PC film.

[0055] The amount of polymer solution used is determined according to the surface area of ​​the hollow SiO2 photonic crystal template and is 0.1 mL / cm 2 .

[0056] Embodiment 4:

[0057] The difference between this embodiment and embodiment 1, embodiment 2 or embodiment 3 is that:

[0058] PMMA@SiO2 core-shell microspheres, PS@TiO2 core-shell microspheres, and PMMA@TiO2 core-shell microspheres were used to replace the PS@SiO2 core-shell microspheres in Example 1 as nano-microspheres for assembly templates, and other conditions were consistent with those in Example 1.

[0059] The present invention uses polymer microspheres as core materials, and uses tetraethyl silicate TEOS to hydrolyze to coat a layer of SiO2 on the surface of the polymer microspheres to prepare core-shell microspheres. The core-shell microspheres are self-assembled to form a photonic crystal template, and the polymer core is removed by calcination to form a hollow SiO2 photonic crystal H-SiO2 PCs template. After the H-SiO2 PCs template is modified with a silane coupling agent, a polymer with flame retardancy and high mechanical strength is filled into its gap to obtain a structural color film for harsh environments. Tests of the film's flame retardancy, tensile strength, high and low temperature resistance, friction resistance, and strong acid and alkali resistance show that it has excellent flame retardancy, structural color stability, and strong acid and alkali resistance. Based on the above excellent performance in harsh environments, this structural color film has broad application prospects in color display in the fields of high temperature resistance, flame retardant protection, and fire passage markings.

[0060] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected according to actual needs within the limited range, and the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the content required to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.

[0061] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A structural color film, characterized in that: It includes a hollow SiO2 photonic crystal template and a high-strength flame-retardant polymer filled in the gap of the hollow SiO2 photonic crystal template; wherein the hollow SiO2 photonic crystal template is modified by a silane coupling agent and then filled with the high-strength flame-retardant polymer.

2. The structural color film according to claim 1, characterized in that: The high-strength flame-retardant polymer is one or a combination of poly(m-phenylene isophthalamide), poly(p-phenylene terephthalamide), and polybenzimidazole.

3. The structural color film according to claim 1, characterized in that: The silane coupling agent is one or a combination of aminopropyltriethoxysilane, methacryloxypropyltrimethoxysilane and methyltrimethoxysilane.

4. The method for preparing a structural color film according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Preparation of hollow SiO2 photonic crystal template; (2) Modifying the hollow SiO2 photonic crystal template using a silane coupling agent; (3) Filling the gaps of the modified hollow SiO2 photonic crystal template with a high-strength flame-retardant polymer and vacuum drying the template to obtain a structural color film.

5. The preparation method according to claim 4, characterized in that: The step (2) specifically comprises: The hollow SiO2 photonic crystal template is placed in a mixed solution of a silane coupling agent, ethanol and water for hydrothermal reaction to obtain a modified hollow SiO2 photonic crystal template.

6. The preparation method according to claim 5, characterized in that: The volume ratio of the silane coupling agent, ethanol and water in the mixed solution is (0.05-0.2):20:(0.5-1.5).

7. The preparation method according to claim 5, characterized in that: The temperature of the hydrothermal reaction is 75-85° C. and the duration is 1-3 hours.

8. The preparation method according to claim 4, characterized in that: The step (3) specifically comprises: Adding a high-strength flame-retardant polymer to an organic solvent and a co-solvent, stirring at 70 to 100° C. for 10 to 20 hours to completely dissolve the polymer, and obtaining a transparent polymer solution with a mass fraction of 8 to 10%, and then filling the gaps of the modified hollow SiO2 photonic crystal template; The organic solvent is one or a combination of N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and hexamethylphosphoramide; the co-solvent is one or a combination of lithium chloride, calcium chloride, sodium hydroxide, and potassium hydroxide.

9. The preparation method according to claim 8, characterized in that: The mass ratio of the organic solvent to the co-solvent is (20-30):

1.

10. The preparation method according to claim 8, characterized in that: The amount of the transparent polymer solution is determined according to the surface area of ​​the hollow SiO2 photonic crystal template and is 0.1-0.3 mL / cm 2 .

Citation Information

Patent Citations

  • Flexible smart film material with photonic band gap structure and preparation method of flexible smart film material

    CN105504318A

  • Polymer-resin inverse-opal-structure material and preparation method thereof

    CN107828078A

  • Preparation method for patterned photonic crystal structural coloration material with stable structure and bright color

    CN109031476A

  • Preparation method of anti-aging flame-retardant decorative photonic crystal structural color film

    CN111849260A

  • Covalent organic framework material with structural color and preparation method thereof

    CN117143387A